Pengaruh Ukuran Perusahaan Dan Profitabilitas Terhadap Kebijakan Dividen Dengan Kebijakan Hutang Hutang Sebagai Variabel Moderasi (Pada Perusahaan IDX30 Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022) - Monica Anggelia; Tatik Zulaika; Oktobria Y.Asi (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to examine the effect of company size and profitability on dividend policy with debt policy as a moderating variable (IDX30 companies listed on the Indonesian stock exchange in 2018-2022). The research method used in this study is quantitative research and uses secondary data collection techniques in the form of an annual report. The sample in this study was selected using a purposive sampling method and a sample of 15 IDX30 companies was obtained that met the sample criteria. The data analysis method used is multiple linear regression analysis and moderated regression analysis. The results of this study indicate that firm size has no effect on dividend policy, and profitability has an effect on dividend policy. Moderation of debt policy weakens the effect of company size on dividend policy. And in moderation the debt policy is not able to weaken the effect of profitability on dividend policy. The coefficient of determination (adjusted R Square) is 0.330 which indicates that company size and profitability on dividend policy is 33% while the remaining 67% (100% - 33%) is influenced by variables outside the research model. After adding debt policy as a moderating variable, the coefficient of determination decreases to 0.321. From these results it can be interpreted that 32.1% of the dividend policy can be explained by the variable company size and profitability with debt policy. While the rest, namely 67.9% (100% - 32.1%) is explained by variables outside the study